Space explorers - Moore, Eva.; Enik, Ted; Cole, Joanna (New York : Scholastic, 2000)
Carlos and his classmates join Ms. Frizzle on an epedition to outer space where they learn about the solar system.
Accelerated Reader AR
Keywords: Field trips -- Juvenile fiction; Outer space -- Juvenile fiction; Adventure stories